An Analytical Study of Communication Challenges Faced by Deaf Children: Barriers, Strategies, and Solutions - Anirudhdhasinh Y. Raulji (International Journal of Children, 2025)
As social beings the use of communication is a basic need that has to be met at all times; however, children with deafness encounter many barriers that prevent them from socializing and to a greater extent integrating into the society. This scholarly research work therefore seeks to examine and synthesise the communication difficulties faced by the young deaf, understand the reasons behind such difficulties, and examine ways by which the communication difficulties could be mitigated. Using both interviews and surveys, the study role of families, educational institutions and communities on the communication experiences of the deaf. Evidential findings that bring out the problematic areas are Delay in diagnosis, restricted access to sign language education, and low community understanding contribute to the growth of effective communication skills. The paper also assesses different approaches such as the application of technology support, sign language and other educational accommodations to the mentioned challenges. Additionally, the study emphasizes how crucial it is to bridge communication gaps through early intervention programs, teacher preparation, and community awareness initiatives. This study intends to assist policymakers, educators, and caregivers in creating comprehensive programs that improve the communication skills of deaf children, guaranteeing equitable opportunity for social integration and academic success by providing inclusive strategies. The research's conclusions offer insightful information for enhancing educational frameworks and raising awareness of deaf children's communication needs.
Keywords: Assistive technologies; Inclusive education; communication challenges; deaf children; sign language; societal awareness